Native country of the heart: A memoir - Moraga, Cherríe (Picador, 2019)
"This memoir's beauty is in its fierce intimacy." –Roy Hoffman, The New York Times Book ReviewOne of Literary Hub's Most Anticipated Books of 2019From the celebrated editor of This Bridge Called My Back, Cherríe Moraga charts her own coming-of-age alongside her mother’s decline, and also tells the larger story of the Mexican American diaspora.Native Country of the Heart: A Memoir is, at its core, a mother-daughter story. The mother, Elvira, was hired out as a child, along with her siblings, by their own father to pick cotton in California’s Imperial Valley. The daughter, Cherríe Moraga, is a brilliant, pioneering, queer Latina feminist. The story of these two women, and of their people, is woven together in an intimate memoir of critical reflection and deep personal revelation. As a young woman, Elvira left California to work as a cigarette girl in glamorous late-1920s Tijuana, where an ambiguous relationship with a wealthy white man taught her life lessons about power, sex, and opportunity. As Moraga charts her mother’s journey―from impressionable young girl to battle-tested matriarch to, later on, an old woman suffering under the yoke of Alzheimer’s―she traces her own self-discovery of her gender-queer body and Lesbian identity, as well as her passion for activism and the history of her pueblo. As her mother’s memory fails, Moraga is driven to unearth forgotten remnants of a U.S. Mexican diaspora, its indigenous origins, and an American story of cultural loss.Poetically wrought and filled with insight into intergenerational trauma, Native Country of the Heart is a reckoning with white American history and a piercing love letter from a fearless daughter to the mother she will never lose.
Keywords: 1900-1999; amériques; approches et analyses; chicanas; histoire et politique; histoire familiale; identités LGBTQIA2+; mexique; mémoire collective; personnes lesbiennes; périodes historiques; queer; régions géographiques; thématiques; états-unis